IL-6 , IL -8, IL -10 LEVEL IN MEN SPERM - Максимюк, Г.В.; Воробець, З.Д.; Максимюк, В.М. (World of Medicine and Biology, 2015)
The research was conducted in order to identify relationship of concentration of inflammatory and anti-inflammatory cytokines to the quality parameters of sperm. The trend to a positive correlation between the concentrations of IL-6 and IL-10 (r = 0,45) and concentration of sperm was found; IL-8 (r = 0,52) to the viscosity of semen, IL-10 (r = 0,50) – to the number of motile cells. Trend to negative correlation between IL-6 (r = -0,42) and IL-8 (r = -0,55) with the number of live spermatozoa was present, but IL-10 (r = -0,70) was close to the volume of semen. Strong positive correlation between concentration parameters of cytokines was observed in groups of IL-8 and IL-6 (r = 0,74) and IL-10 and IL-6 (r = 0,72) in the researched semen ejaculates. The studies suggest that increased concentration of IL-6 and IL-8 results in decreasing semen quality. This might be related to the processes that lead to men infertility. The increased concentration of IL-10 in the ejaculates optimizes the parameters of spectrogram.